Synthesis of new Polyimides Derived from 4- minoantipyrine (Baghdad Science Journal, 2025)
In the present study, new five polymers of acryloyl chloride have been synthesized by reaction 4-aminoantipyrine with many substituted acid chloride (A-E). Then condensation of polyacryloyl chloride with the product in one step (A-E), in a suitable solvent in the presence amount of (Et3N) to obtain new polyimides(A1-E5). The prepared compounds were characterized by UV. FT-IR, 1H-NMR and 13C-NMR spectroscopy and measuring of other physical properties such as softening point, melting point and solublities.